2002
DOI: 10.2176/nmc.42.293
|View full text |Cite
|
Sign up to set email alerts
|

Severe Papilledema Identified 3 Weeks After Head Injury. Case Report.

Abstract: A 62-year-old woman presented with rapidly developed visual disturbance without associated headache or nausea 3 weeks after head injury. Ophthalmologic examination revealed bilateral severe papilledema with retinal hemorrhage, and intracranial pressure (ICP) was 17.5 cmH 2 O estimated by lumbar puncture. Computed tomography and magnetic resonance (MR) imaging showed no evidence of increased ICP, except dilation of the subarachnoid space around the optic nerves with distortion of the nerves. Her visual acuity r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 8 publications
1
2
0
Order By: Relevance
“…It is consistent with findings of MasilaEtal [8] Papilloedema is generally due to secondary manifestations of cerebral injury producing raised intracranial tension. This is well co-related withYadama SM ,etal [14] who reported that papilloedema may occur due to mildly raised ICP and trapped subarachnoid CSF around the optic nerve.kulkarny et al [1] reported 5.8% incidence of papilloedema. Pre retinal Hemorrhage and Vitreous hemorrhage was seen in 4% and 1% cases respectively.It was almost similar as in other studies.…”
Section: Discussionsupporting
confidence: 56%
“…It is consistent with findings of MasilaEtal [8] Papilloedema is generally due to secondary manifestations of cerebral injury producing raised intracranial tension. This is well co-related withYadama SM ,etal [14] who reported that papilloedema may occur due to mildly raised ICP and trapped subarachnoid CSF around the optic nerve.kulkarny et al [1] reported 5.8% incidence of papilloedema. Pre retinal Hemorrhage and Vitreous hemorrhage was seen in 4% and 1% cases respectively.It was almost similar as in other studies.…”
Section: Discussionsupporting
confidence: 56%
“…Over the two recent decades, there have been anecdotal reports on bilateral papilledema in patients with CSDH [19,20,21]. Bilateral papilledema in patients with CSDH may be caused by an increased gradient of pressure between the subarachnoid space around the bilateral optic nerves and the intracranial subarachnoid space [15]. The difference in age structure of the study sample and early diagnosis of CSDH are likely to explain the difference in the reported incidence of papilledema in patients with CSDH between studies.…”
Section: Discussionmentioning
confidence: 93%
“…Studies vary in the reported incidence of papilledema in patients with CSDH. It has been reported that the incidence of papilledema in patients with CSDH in the studies conducted before the nineteen nineties ranged from 20% to 75% [11][12][13][14][15][16], and in more recent studies was as low as 0.4%-2% [17,18]. Over the two recent decades, there have been anecdotal reports on bilateral papilledema in patients with CSDH [19,20,21].…”
Section: Discussionmentioning
confidence: 99%